Species distribution modeling allied with land-use reveal priority sites and species for palm (Arecaceae) conservation in Rio de Janeiro, Brazil - de Lima, Thales Moreira; Portela, Rita De Cássia Quitete; Mendes, Eduardo Teles Barbosa; Oda, Gabriela Akemi (Frontiers in Forests and Global Change, 2022)
Palms species (Arecaceae) are abundant in tropical forests and influence ecosystems in important ways. Moreover, they are a relevant feature in the Atlantic Forest biodiversity hotspot. In this study, we seek to better understand the distribution of palm richness in Rio de Janeiro state, Brazil, with the aim to support conservation decisions and actions. Maps for 15 palm species were generated through species distribution modeling and then stacked into a palm richness map, which was further combined with current land-use and protected area maps to generate a realistic portrayal of the current situation of Arecaceae in the state. Our results revealed an increasing inland-to-coast pattern of richness that matches the biogeographical subdivision of the Atlantic Forest. Considering the land-use information, the palm species potential distribution is drastically reduced, especially for some species which already have a restricted distribution in the state. We also identified the most relevant protected areas for the conservation of palms in the state and those which might have been overlooked in floristic inventories, thus requiring more detailed investigation. Moreover, we point out those species with few points, for which species distribution models could not be built, and argue that they are the ones more likely to be threatened by habitat loss and should be the focus of specimen collection and recording. Finally, we draw attention to a large medium-richness remnant located between two protected areas which probably functions as a connection between them and should be a priority area for conservation.